Using Flashcard as A Media In Teaching Vocabulary For The Eighth Grade Students Of Junior High School - Elsa Matruty; Stella Rose Que (MATAI: International Journal of Language Education, 2021)
The problem of this study was the students’ vocabulary mastery was still low. This study aims to improve student's vocabulary by using Flash Card for the eighth-grade students of SMP Kristen 1 Dobo. One alternative to facilitating students' problems is by using Flashcards. Flashcards can be used as medium and visual aids that are interesting and helpful for the students and teacher during the teaching-learning process. Vocabulary is essential for students in learning English as a foreign language. Vocabulary is a fundamental and essential thing to know. The purpose of learning Vocabulary is to help the students to be able to communicate and help the students to reflect on their experience, show idea, feelings and also understand any kind of meaning. Common vocabulary will obstruct the students' speaking, listening, reading, or writing. Therefore, the students need to learn vocabulary before the four skills.